Exploring naturally occurring ivy nanoparticles as an alternative biomaterial. (1st October 2015) - Huang, Yujian; Wang, Yi-Jun; Wang, Yongzhong; Yi, Sijia; Fan, Zhen; Sun, Leming; Lin, Derrick; Anreddy, Nagaraju; Zhu, Hua; Schmidt, Michael; Chen, Zhe-Sheng; Zhang, Mingjun
Graphical abstract: Abstract: Arabinoglactan protein (AGP)-rich nanoparticles obtained from the sticky exudates of Hedera helix (English ivy), have shown promising potential to be used in nanomedicine owing to their excellent aqueous solubility, low intrinsic viscosity, biocompatibility, and biodegradability. In this study, the feasibilities of utilizing ivy nanoparticles (INPs) as nano-carriers for delivering chemotherapeutic drugs in cancer therapy and as nano-fillers to develop novel scaffolds for tissue engineering in regenerative medicine are evaluated. Via electrostatic and hydrophobic interactions, pH-responsive nanoconjugates are formed between the INPs and the doxorubicin (DOX) with an entrapment ratio of 77.9 ± 3.9%. While the INPs show minimal cytotoxicity, the formed INP-DOX conjugates exhibit substantially stronger cytotoxic activity than free DOX against multiple cancer cell lines, suggesting a synergistic effect is established upon conjugation. The anti-cancer effects of the INP-DOX conjugates are further evaluated via in vivo xenograft assays by subcutaneously implanting DOX resistant cell line, SW620/Ad-300, into nude mice. The tumor volumes in mice treated with the INP-DOX conjugates are significantly less than those of the mice treated with free DOX. In addition, the INPs are further exploited as nano-fillers to develop fibrous scaffolds with collagen, via mimicking the porous matrix where the INPs are embedded under natural condition. Enhanced adhesion of smooth muscle cells (SMCs) and accelerated proliferation of mouse aortic SMCs are observed in this newly constructed scaffold. Overall, the results obtained from the present study suggest great potential of the INPs to be used as biocompatible nanomaterials in nanomedicine. The AGP-rich INP renders a glycoprotein architecture that is amenable for modification according to the functional designs, capable of being developed as versatile nanomaterials for extensive biomedical applications. Statement of Significance: Naturally occurring organic nanomaterials have drawn increasing interest for their potential biomedical applications in recent years. In this study, a new type of naturally occurring nanoparticles obtained from the sticky exudates on the adventitious roots of English ivy ( H. helix ), was explored for its potential biomedical application. In particular, the feasibilities of utilizing ivy nanoparticles (INPs) as nano-carriers for delivering chemotherapeutic drugs in cancer therapy and as nano-fillers to develop novel scaffolds for tissue engineering in regenerative medicine were evaluated both in vitro and in vivo . Overall, the results obtained from the present study suggest the great potential of the INPs to be used as biocompatible nanomaterials in nanomedicine. This study may open a totally new frontier for exploring the biomedical application of naturally occurring nanomaterials.